РАСПРОСТРАНЕНИЕ ШАКАЛА (Canis aureus L., 1758) В ЗАИЛИЙСКОМ АЛАТАУ (Experimental biology, 2009)
The data on jackal’s spreading in Zailliyskii Alatau are given for the first time in this article. The jackals have penetrated from the Ily river basin to Zailliyskii Alatau by two ways: оne of them runs along the flood-lands of Kurti and Kaskelen Rivers and the second one along Shelek and Turguen Rivers.
Keywords: jackal’s spreading